Relationships Between Infection, Dissemination, and Transmission of West Nile Virus RNA in Culex pipiens quinquefasciatus (Diptera: Culicidae) - Richards, Stephanie L. (2012)
Culex pipiens quinquefasciatus Say fed blood containing 6.8 ± 0.3 logs (mean ± SE) plaque-forming units of West Nile virus (WNV)/ml were maintained at 28°C for incubation periods (IP) of 7, 14, or 21 d. Several attributes of vector competence were determined at each IP using quantitative real-time reverse transcriptase polymerase chain reaction to estimate plaque forming unit equivalents including: infection rate (WNV-positive abdomens), dissemination rate (WNV-positive legs or thoraces), combined dissemination rate (WNV-positive legs and thoraces), transmission rate (WNV-positive saliva), and WNV titers in abdomens, legs, thoraces, and saliva. Each rate increased or was equivalent with increasing IP. Mosquitoes transmitting WNV in saliva also had significantly higher IP-dependent WNV titers in abdomens, legs, and thoraces. Titers of WNV in abdomens were significantly correlated with titers in legs and thoraces, but the degree of association changed with IP. However, titers of abdomens, legs, and thoraces were not correlated with WNV presence or titer in the saliva. The results show that WNV presence or titer in the saliva of infected Cx. p. quinquefasciatus was not directly influenced by processes involved in WNV replication in other tissues. The processes controlling midgut infection and escape are, in part, independent from the infection processes in other tissues. The relationship between infection, dissemination, and transmission varied over time. The infection and replication of WNV in different tissues is likely influenced by different barriers encountered during the extrinsic incubation period. The significance of these observations for understanding vector competence is discussed.